Islam in Minangkabau from Conflict to Integrity - Qisthi, Ihya; Erman, Erman; Fauzi, Muhammad; Zulfan, Zulfan (JUSPI (Jurnal Sejarah Peradaban Islam), 2025)
This article explains how the development of Islam in Minangkabau acculturated with customs, until the emergence of Islamic reformers who had a major influence on the world of education in Minangkabau which previously had a conflict between the tuo and the mudo because of the differences in paradigms between them in understanding and implementing customs and religion. This study aims to determine the process of the entry of Islam and its development until it merged with customs in Minangkabau. This study uses a historical qualitative approach by looking at the social context that occurred in Minangkabau society by looking at library data related to Minangkabau and Islam. The development of Islam in Minangkabau was not as smooth as imagined. Although the Minangkabau people have accepted Islamic teachings as an official religion by looking at the Minangkabau proverb "Adat basandi syarak, syarak basandi kitabullah", there are several customary practices that are not in line with Islamic teachings that give rise to conflict as evidenced by the Paderi War in Minangkabau. In the period after the Padri War, Islamic reformers were born who gave birth to integrity and had a big influence on the Islamic world in Minangkabau, especially in terms of education, which was proven by the birth of many madrasas and made Minangkabau a region that was strong in Islamic teachings, according to sharia.